Growers’ Knowledge of Improved Maize Production Technologies in Jammu Region of J&K (Indian Journal of Extension Education, 2020)
Knowledge is one of the important components of behaviour as such it plays an important role in the covert and overt behaviour of an individual. Knowledge as defined in present study included those behaviours and test situations which emphasised the remembering either by recognition or recall of ideas, material or phenomena about maize production technology. The study was conducted in five districts namely Doda, Kathua, Poonch, Rajouri and Udhampur of Jammu region of Jammu and Kashmir. A sample of 220 maize growers was selected by multi-stage random sampling from 22 villages of 11 tehsils of 5 selected districts. Data were collected by personal interview method. A knowledge test was developed with items related to different maize production technologies. It was measured with the scores obtained by the maize growers in the test. 47 per cent of the respondents had medium level of knowledge whereas 38 per cent had low level of knowledge. There was significant difference in mean knowledge score between farmers of districts Udhampur -Doda, Poonch -Doda, Doda -Kathua and Rajouri - Kathua. More awareness programmes should be organized to increase knowledge level of maize growers regarding maize cultivation practices which may help to enhance the production of maize in the region.